Circulation Of Food And Beverage Products Without Labels In The Study Of Criminal Law - Bambang Indra Agung (International Asia Of Law and Money Laundering (IAML), 2022)
The large number of food and beverage products in circulation do not meet the requirements and standards set forth in the law can be a problem and endanger human safety. Therefore, the existence of distribution permits and supervision of food and beverage products is very important to maintain food and beverage safety. The observation method used is normative juridical law observation, which is a literature observation by examining library materials related to the object under study. In this observation using the approach of legislation (statute approach). Observations used in the form of qualitative observations. The results showed that before the food and beverage industry products circulated must have a distribution permit, if it is ignored will be subject to criminal sanctions and administrative sanctions. The purpose of supervision is to provide consumer protection and prevent the circulation of food that endangers consumers. Surveillance is carried out preventively and repressively. So it is very important that there is supervision and firmness of officers in overseeing the distribution of food and beverage products that do not have labels. So that consumers know more about the information of food and beverage products that they will consume clearly.